A rational study on the geometric and electronic properties of single-atom catalysts for enhanced catalytic performance. Issue 45 (17th November 2020) - Xue, Qi; Xie, Yi; Wu, Simson; Wu, Tai-Sing; Soo, Yun-Liang; Day, Sarah; Tang, Chiu C.; Man, Ho W.; Yuen, Sha T.; Wong, Kwok-yin; Wang, Ying; Lo, Benedict T. W.; et al.
Abstract : We investigate the geometric and electronic properties of single-atom catalysts (SACs) for electrocatalytic CO2 reduction reaction (eCO2 RR). Abstract : We investigate the geometric and electronic properties of single-atom catalysts (SACs) within metal–organic frameworks (MOFs) with respect to electrocatalytic CO2 reduction as a model reaction. A series of mid-to-late 3d transition metals have been immobilised within the microporous cavity of UiO-66-NH2 . By employing Rietveld refinement of new-generation synchrotron diffraction, we not only identified the crystallographic and atomic parameters of the SACs that are stabilised with a robust M⋯N(MOF) bonding of ca . 2.0 Å, but also elucidated the end-on coordination geometry with CO2 . A volcano trend in the FEs of CO has been observed. In particular, the confinement effect within the rigid MOF can greatly facilitate redox hopping between the Cu SACs, rendering high FEs of CH4 and C2 H4 at a current density of −100 mA cm −2 . Although only demonstrated in selected SACs within UiO-66-NH2, this study sheds light on the rational engineering of molecular interactions(s) with SACs for the sustainable provision of fine chemicals.